Initial UK Experience With a Novel Magnetic Transcutaneous Bone Conduction Device. Issue 8 (September 2015) - Carr, Simon D.; Moraleda, Javier; Procter, Vicky; Wright, Kay; Ray, Jaydip
<x xml:space="preserve">Abstract</x> Objective To assess outcomes with a new transcutaneous bone conduction hearing aid. Patients Patients that underwent implantation with the transcutaneous bone conduction device between November 2013 and May 2014. Intervention Hearing rehabilitation using the BAHA Attract. Main Outcome Measures Quality of life measures using Glasgow benefit inventory (GBI) and clinically oriented scale of improvement (COSI). Audiological outcome using word discrimination score. Results Ten patients were implanted. Significant improvement in GBI and COSI scores comparing preimplantation and postimplantation. An increase in word discrimination scores at 30 dBA, with an increase from 0% unaided to a mean of 50% with the magnetic transcutaneous bone conduction aid and at 50 dBA with an increase from a mean of 31.7% to 88.3%. However, the word discrimination score increase at 30, 50, and 60 dBA was not statistically significant (p = 0.25; Wilcoxon). Conclusion There was a high level of satisfaction with the device with significant increases in GBI and COSI scores in patients who were previously aided with an acoustic aid. The absence of daily skin hygiene appealed to patients.